Surat dari Keluarga Korban Tragedi Trisakti, Mei 1988 - Supriyadi (Indonesia, 2011)
On May 1998, Indonesian students gathered to demand changes in the government. The demonstrations were stopped by the new regime and four Trisakti students were killed by army and police fire. 13 years later, the families still demand justice but the government refuses to assume responsibility.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films